The Home school learning space experiences and interior design strategies of selected homeschooling families in the Philippines - Torres, Johann Marie L. (College of Home Economics, University of the Philippines Diliman, 2021)
An optimal learning environment for a homeschooling family is needed to provide physical and emotional comfort, social support, and most of all, effective cognitive learning. In designing a homeschool learning space, therefore, the learning principles and different ethodologies and activities should be incorporated into the space the most, aside from providing spatial solutions, organization, flexibility, and comfort, especially with the trends in learning spaces: shift of teaching principles, digital technology, and different views of learning. As a response, this study aimed to understand the different educational philosophies and homeschool approaches for a more personalized learning environment. A qualitative study was conducted through an online survey conducted via Facebook and 54 homeschooling families answered the questionnaire. The results showed the different experiences and interior design strategies of selected homeschooling families, their reasons for homeschooling, principles and methods used, challenges in a homeschool learning space, and the furnishings, furniture, equipment, and decor used. Through analyzing the results of the study using humancentered design theory, an understanding of how homeschooling families use their spaces to suit their needs and homeschooling philosophies were gained and common spatial and cognitive needs were derived. Commonalities on how the homeschooling families arranged their spaces, the different materials, equipment, and accessories used were seen. By relating it into their homeschooling principles and methodologies, this study showed that when their learning space incorporated all these elements, it may provide a better cognitive learning for the homeschooling child(ren). The results of this research showed that an organized, flexible, and comfortable learning environment provide a conducive space for the homeschooling child(ren) to learn and the families to engage with different activities to support learning. To further enhance their learning spaces, homeschooling families may also adapt interior design strategies that align with their homeschooling principles.